Software framework for distributed experimental?computational simulation of structural systems. - Takahashi, Yoshikazu (Earthquake engineering & structural dynamics.)
Supported by the recent advancement of experimental test methods, numerical simulation, and high-speed communication networks, it is possible to distribute geographically the testing of structural systems using hybrid experimental?computational simulation. One of the barriers for this advanced testing is the lack of flexible software for hybrid simulation using heterogeneous experimental equipment. To address this need, an object-oriented software framework is designed, developed, implemented, and demonstrated for distributed experimental?computational simulation of structural systems. The software computes the imposed displacements for a range of test methods and co-ordinates the control of local and distributed configurations of experimental equipment. The object-oriented design of the software promotes the sharing of modules for experimental equipment, test set-ups, simulation models, and test methods. The communication model for distributed hybrid testing is similar to that used for parallel computing to solve structural simulation problems. As a demonstration, a distributed pseudodynamic test was conducted using a client?server approach, in which the server program controlled the test equipment in Japan and the client program performed the computational simulation in the United States. The distributed hybrid simulation showed that the software framework is flexible and reliable.